Pengembangan Minuman Jahe, Sereh dan Lemon sebagai Produk UMKM di Sekolah SMP Insan Cendekia Mandiri Boarding School Sidoarjo, Jawa Timur - Putri, Cantika Aura; Lutviani, Diah; Nugraha, Dimas Anggun; Hamdani, Muhammad Yusuf; 'Ilmi, Zujajatul (Indonesia Berdaya, 2025)
Abstract. This Community Service activity was held at the Insan Cendekia Mandiri Islamic Boarding School Junior High School in Sidoarjo, East Java. The main objective was to equip students with entrepreneurial skills, specifically in developing herbal drinks made from ginger, lemongrass, and lemon, utilizing the potential of the school's land. The novelty of this activity lies in the integration of local resources (herbal plants) into competitive MSME products, while also building student independence in procuring raw materials through planting practices. The method we employed involved a series of stages: a pre-test to measure students' initial understanding of entrepreneurship, followed by a Business Model Canvas (BMC) conceptual briefing, hands-on practice in making herbal drinks, and practical experience planting ginger, lemongrass, and lemon. The final stage was a post-test to begin developing students' understanding. The results showed a significant increase in students' understanding of business concepts and practical skills in producing herbal drinks. Furthermore, students gained knowledge about plant cultivation as a means of procuring raw materials. This activity significantly contributed to fostering students' entrepreneurial spirit and opening up opportunities for them to develop MSME products based on local potential.  Abstrak. Kegiatan Pengabdian Masyarakat ini dilaksanakan di SMP Insan Cendekia Mandiri Boarding School, Sidoarjo, Jawa Timur. Tujuan utama pelaksanaan ini adalah untuk membekali siswa dengan kemampuan kewirausahaan, khususnya dalam pengembangan minuman herbal berbahan dasar jahe, sereh, dan lemon, dengan memanfaatkan potensi lahan sekolah. Kebaruan dari kegiatan ini terletak pada integrasi pemanfaatan sumber daya lokal (tanaman TOGA) menjadi produk UMKM yang berdaya saing, serta membangun kemandirian siswa dalam pengadaan bahan baku melalui praktik penanaman. Metode yang kami terapkan meliputi serangkaian tahapan: diawali dengan pre-test untuk mengukur pemahaman awal siswa mengenai kewirausahaan , dilanjutkan dengan penyuluhan konsep Business Model Canvas (BMC) , praktik langsung pembuatan minuman herbal , serta praktik penanaman jahe, sereh, dan lemon. Tahap akhir adalah post-test untuk mengevaluasi peningkatan pemahaman siswa. Hasil yang diperoleh menunjukkan peningkatan signifikan dalam pemahaman siswa mengenai konsep bisnis dan keterampilan praktis dalam memproduksi minuman herbal. Selain itu, siswa juga mendapatkan pengetahuan mengenai budidaya tanaman sebagai upaya keberlanjutan penyediaan bahan baku. Kegiatan ini memberikan kontribusi nyata dalam menumbuhkan jiwa kewirausahaan siswa dan membuka peluang mereka untuk mengembangkan produk UMKM berbasis potensi lokal.